2017
DOI: 10.1159/000480694
|View full text |Cite
|
Sign up to set email alerts
|

An Echocardiographic Screening Program Helps to Identify Pulmonary Hypertension in Extremely Low Birthweight Infants with and without Bronchopulmonary Dysplasia: A Single-Center Experience

Abstract: Background: Pulmonary hypertension (PH) affects 1 in 6 infants with a birthweight <1,000 g (extremely low birthweight; ELBW) and is frequently associated with bronchopulmonary dysplasia (BPD). If untreated, the mortality rates of the disease are high. Objectives: The aim of this study was to characterize risk factors for PH in ELBW infants and to describe the timing of onset of the disease by setting up a screening program. Methods: ELBW infants treated at the Department of Neonatology (level III neonatal inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The relationship between severity of BPD and PH has been variable in the literature. Few studies could not find an association with PH and severity of BPD . In contrast, Bhat et al reported PH in 24/26 cases (92%) with moderate to severe BPD .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The relationship between severity of BPD and PH has been variable in the literature. Few studies could not find an association with PH and severity of BPD . In contrast, Bhat et al reported PH in 24/26 cases (92%) with moderate to severe BPD .…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of PH at enrollment in our cohort (28.5%) is difficult to compare to “early” PH in prior studies as our cohort's first echocardiogram was completed after 28 days of life timed with initial diagnosis of BPD. In a cohort study of extremely low birth weight infants with BPD, screening echocardiogram detected PH in 18% infants with 10.6% diagnosed before discharge and 7.4% cases diagnosed at screening 3‐6 months after discharge . It is unclear whether these patients had other factors that contributed to the delayed onset of their pulmonary vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…BPD is the most common morbidity of children born <30 weeks’ gestation and remains the most common lung disease of infancy . BPD is diagnosed in roughly 40% of infants born ≤28 weeks gestational age, which results in 10 000‐15 000 new cases in the USA each year . While knowledge of the pathophysiology and pathobiology of BPD continues to evolve, BPD is defined as a chronic lung disease in preterm infants born ≤32 weeks’ gestation who require ongoing oxygen therapy at 36 weeks’ postconceptual age .…”
Section: Neonatal Phmentioning
confidence: 99%
“…22 BPD is diagnosed in roughly 40% of infants born ≤28 weeks gestational age, which results in 10 000-15 000 new cases in the USA each year. [22][23][24][25][26] While knowledge of the pathophysiology and pathobiology of BPD continues to evolve, BPD is defined as a chronic lung disease in preterm infants born ≤32 weeks' gestation who require ongoing oxygen therapy at 36 weeks' postconceptual age. 23,27 The pathophysiology is characterized by a uniform arrest of lung development and dysmorphic pulmonary capillaries.…”
Section: Bronchopulmonary Dysplasia-related Phmentioning
confidence: 99%
“…The study by Mehler et al [16] in this issue of Neonatology prospectively evaluated 360 ELBW preterm infants for echocardiographic signs of PH. Infants with BPD were evaluated at 36 weeks' PMA while those without BPD were studied shortly before discharge.…”
mentioning
confidence: 99%